Inequality of earnings - Dennis J. Snower (Centre for Economic Policy Research (CEPR), 1999)
This Paper surveys major empirical regularities concerning changes in earnings inequality in Europe and the US over the past 25 years. Next, it indicates which of these regularities can be explained within the competitive demand–supply framework of analysis and what is left unexplained. Finally, it considers the implications of organizational change as a possible rationale for recent inequality developments.
Keywords: D23; D24; D31; D33; D63; 330; income distribution; earnings; wage rigidities; skilled and unskilled workers; education; globalization; technological change; organizational change; labour supply; minimum wage; unionization; inequality; Einkommensverteilung; Organisatorischer Wandel; Vergleich; USA; EU-Staaten